DIALOGUE BETWEEN HUMANS AND NATURE IN MUSTARI'S SHORT STORY “UCUK SEKOLAH LAGI” (GLOTFELTY ECOCRITICISM REVIEW) - Kusumawati, Aning Ayu (Prosiding Konferensi Internasional Kesusasteraan, 2025)
Mustari's short story “Ucuk at School Again” (“Ucuk Sekolah Lagi”) captures the dynamics of life in a coastal community through the experiences of a child, Ucuk, who leaves school to go fishing. A turning point occurs when he encounters a storm at sea; this ecological experience fosters a new awareness of the importance of education. This study utilizes Cheryll Glotfelty's ecocritical theory, which emphasizes the reciprocal relationship between humans and the environment in literary works. The research method used is qualitative-descriptive, examining the representation of characters and the ecological setting in the short story. The results show that nature in the short story functions as an active subject that shapes the characters' consciousness. For Ucuk, the sea and storms act as frightening "ecological teachers," forcing him to transition from the world of hard work to school. For fishermen, the sea is both a source of livelihood and a space of risk, where dependence on nature creates solidarity but also creates uncertainty. Meanwhile, Ucuk's mother is depicted interacting with nature through domestic and productive work, such as catching anchovies and making a boat roof from coconut leaves. These activities emphasize women's role in supporting the coastal family economy through the simple yet vital use of natural resources. Thus, this short story demonstrates a dialectical dialogue between humans and the environment, presenting the sea as a setting and an agent of transformation of values, ethics, and life orientations. This study confirms that local literary works such as ”Ucuk Sekolah Lagi” can be read through ecocriticism to understand complex ecological relationships while simultaneously instilling awareness of education, local wisdom, and sustainability in coastal communities.